2018
DOI: 10.1111/radm.12318
|View full text |Cite
|
Sign up to set email alerts
|

A rolling stone gathers no moss: the effect of customers' perceived business model innovativeness on customer value co‐creation behavior and customer satisfaction in the service sector

Abstract: Both researchers and practitioners have been focusing extensively on business model innovation, as it has shown to positively influence business performance. Although the effect of business model innovativeness on customer behavior might be an important mediator between business model innovation and business performance, it has not yet been analyzed. In line with recent calls to consider the customer side in business model innovation research, our paper addresses this problem by studying the influence of custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 92 publications
(152 reference statements)
4
55
0
Order By: Relevance
“…In line with this statement, the business model literature has attempted to answer the questions of how firms function and how they create value [16]. Over the years, a consensus has emerged among scholars that business models consist of three interrelated dimensions, describing the configuration of how value is proposed, created and captured [17][18][19][20][21][22]. Value proposition describes the composition of the product/service portfolio and activities regarding new developments and offerings, the firm's role in production or service delivery, and how (i.e., through which channels) and to whom the firm's offerings are made available [20] 1 .…”
Section: A Business Model and Bmimentioning
confidence: 99%
“…In line with this statement, the business model literature has attempted to answer the questions of how firms function and how they create value [16]. Over the years, a consensus has emerged among scholars that business models consist of three interrelated dimensions, describing the configuration of how value is proposed, created and captured [17][18][19][20][21][22]. Value proposition describes the composition of the product/service portfolio and activities regarding new developments and offerings, the firm's role in production or service delivery, and how (i.e., through which channels) and to whom the firm's offerings are made available [20] 1 .…”
Section: A Business Model and Bmimentioning
confidence: 99%
“…In the context of GOSC, user gratifications manifest in different angles. For example, recent studies have shown that many other factors, such as rich user experience [74][75][76][77][78], and value-added customer services [79][80][81] exert powerful impacts on users' behaviors, since more and more customers prefer to receive gratification from different channels, in addition to having it through price value only. However, this study suggests that promotion strategies, such as discount and red envelopes, can raise the perceived price value of products in GOSC, thus, retaining consumers' platform usage in the long run.…”
Section: The Linkage Between Cognitive/emotional States and Consumer mentioning
confidence: 99%
“…It is requiring new organizational forms (e.g. agile teams -see Brand et al in Since 2010, research on innovation and knowledge in diverse fields has burgeoned (Bouncken and Aslam 2019;Grewal et al 2018;Grigoriou and Rothaermel 2017;Roy and Sarkar 2016) and includes work focused on business models (Clauss et al 2018b;Foss and Saebi 2017;Laamanen et al 2018). Yet, only scant research is located at the interface of digitalization, business models, and their relationship to innovation and knowledge.…”
Section: Introductionmentioning
confidence: 99%